Taxonomy of the Mexican species of Thyreocephalus Guérin-Méneville Coleoptera: Staphylinidae, Xantholinini) - Márquez, Juan; Asiain, Julieta (Zootaxa, 2016)
Mexican species of Thyreocephalus were analyzed taxonomically based on review of 125 specimens in eight entomological collections. We propose that T. dugesi (Casey, 1906) could be a junior synonym of T. scutellaris (Sharp, 1885), but refrain from formal changes until the types can be examined. Thyreocephalus arizonicus Smetana, 1982 is recorded for the first time from Mexico in the states of Estado de México, Jalisco and Morelos. Currently nine species are recorded from Mexico, which is the most species-rich country on the American continent. Five closely related species are included in the "puncticeps" species group recognized and proposed here. A key for species, supported with illustrations of the principal diagnostic structures is provided, as well as redescriptions or diagnoses, and taxonomic discussions for each species. Recognized distribution patterns are briefly discussed.